Onlinization Tafsir: Studi Alquran di Era Disrupsi - Maulana, Helmi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
The emergence and popularity of the internet also gave birth to the phenomenon of online interpretation of interpretation. The era of disruption forces every individual to change and leave old patterns to new patterns that are considered in accordance with the development of communication and information technology. Departing from this reality, this article examines how the presence of online interpretation has the opportunity to develop patterns of interpretation study and research as well as its challenges. This article uses a qualitative research model by analyzing primary data about the concept of online interpretation, its opportunities and hands in the study of interpretation, and its implications. The result is that the interpretation website as a form of online interpretation is big data that can be used as a research source. Multidisciplinary opportunities, easy and cheap, as well as the popularity of interpretation. The challenges are around data understanding, research ethics and methodology. It is necessary to follow up with policy makers so that the prospect of an interpretation study finds its footing in the era of disruption.